2020
DOI: 10.3390/ijms21114115
|View full text |Cite
|
Sign up to set email alerts
|

Minor Splicing Factors Zrsr1 and Zrsr2 Are Essential for Early Embryo Development and 2-Cell-Like Conversion

Abstract: Minor splicing plays an important role in vertebrate development. Zrsr1 and Zrsr2 paralog genes have essential roles in alternative splicing, mainly participating in the recognition of minor (U12) introns. To further explore their roles during early embryo development, we produced Zrsr1mu and Zrsr2mu mutant mice, containing truncating mutations within the second zinc finger domain. Both homozygous mutant mice were viable with a normal lifespan. When we crossed a homozygous Zrsr2mu/mu female with Zrsr1mu/mu mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 57 publications
(90 reference statements)
1
15
0
1
Order By: Relevance
“…This is consistent with the phenotypes observed in reproductively aging mice with a reduced blastocyst rate and increased apoptotic cells in blastocysts. Recently, evidence has suggested that alternative splicing may be closely related to preimplantation embryonic development, suggesting that splicing may play a key role in regulating early embryonic development (Gómez‐Redondo et al, 2020 ; Xing et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the phenotypes observed in reproductively aging mice with a reduced blastocyst rate and increased apoptotic cells in blastocysts. Recently, evidence has suggested that alternative splicing may be closely related to preimplantation embryonic development, suggesting that splicing may play a key role in regulating early embryonic development (Gómez‐Redondo et al, 2020 ; Xing et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Primer sequences are provided in Supplementary Table S1 . Expression levels were normalized against that of the endogenous controls H2afz and Actb as described previously [ 43 , 44 ]. PCR conditions were optimized to achieve efficiencies close to 1.…”
Section: Methodsmentioning
confidence: 99%
“…To calculate ΔΔCT, the highest sample ΔCT value (i.e., the sample showing the lowest target expression) was used as an arbitrary constant to subtract from all other ΔCT sample values. Fold changes in relative gene expression levels of target genes were determined using the formula 2−ΔΔCT [ 67 ]. Gene expression levels were then normalized to those of Actb and H2afz .…”
Section: Methodsmentioning
confidence: 99%